1985
DOI: 10.1145/3959.3961
|View full text |Cite
|
Sign up to set email alerts
|

Disk cache—miss ratio analysis and design considerations

Abstract: The current trend of computer system technology is toward CPUs with rapidly increasing processing power and toward disk drives of rapidly increasing density, but with disk performance increasing very slowly if at all. The implication of these trends is that at some point the processing power of computer systems will be limited by the throughput of the input/output (I/O) system.A solution to this problem, which is described and evaluated in this paper, is disk cache. The idea is to buffer recently used portions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…These results are at odds with Smith's study of caching on a mainframe [8] where he indicated that large blocking factors greatly reduce caching benefits for sequential files. This experiment is also significant because the percent savings is also steeply increasing for the RAM disk which does not do I/O at all.…”
Section: Ram-diskmentioning
confidence: 78%
See 1 more Smart Citation
“…These results are at odds with Smith's study of caching on a mainframe [8] where he indicated that large blocking factors greatly reduce caching benefits for sequential files. This experiment is also significant because the percent savings is also steeply increasing for the RAM disk which does not do I/O at all.…”
Section: Ram-diskmentioning
confidence: 78%
“…Interestingly, on a PC it makes little sense to have more than one set of buffers for a file because there is no concurrent CPU and I/O possible under DOS. This aspect of disk access avoidance is mentioned because Smith [8] found that file blocking loses some of its performance advantages when caching is in effect.…”
Section: Dos Buffersmentioning
confidence: 99%
“…It has already been proved that caching is a good solution to increase the performance of disk operations [8]. In our scenario, a cache for swapped pages should also increase the swapping performance, if a few problems could be solved.…”
Section: Basic Ideamentioning
confidence: 92%
“…Smith [1] considered a number of design parameters for such a disk cache, including cache location, cache size, replace algorithms, block sizes, access time, bandwidth, consistency, error recovery, etc. Each of these parameters was discussed and/or evaluated in terms of trace driven simulations.…”
Section: Introductionmentioning
confidence: 99%